If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -2 = 13 Reorder the terms: -2 + 5p = 13 Solving -2 + 5p = 13 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5p = 13 + 2 Combine like terms: -2 + 2 = 0 0 + 5p = 13 + 2 5p = 13 + 2 Combine like terms: 13 + 2 = 15 5p = 15 Divide each side by '5'. p = 3 Simplifying p = 3
| 6+10+2=210 | | 25-4x=55 | | 2+3y=17 | | -4w+2(w-7)=-16 | | x^2=3z+18 | | 2(X^2)+X=.44 | | 2x-4y+3=19 | | .5x+5=8.5 | | 6x8/15 | | 4/w=-8 | | x^4+3x^3-9x^2-23x-12=0 | | y=x^4+3x^3-9x^2-23x-12 | | 1/2a+1/4b-1/4a+3/4b | | qd=1600-50p | | 3t/10=6 | | (y^7)/(y+2)*(8y+16)/(y^9) | | q=100+5p | | m^4-38m^2+72= | | q=20+p | | x+9+x+12+x-3=180 | | x^2+2=12 | | -17-5x=2x+10 | | x+20+2x-11+90=180 | | 8x-(4x+4)=16 | | Log(x+12)-logx=1 | | x+13+2x+2x-8=180 | | X=9y+3 | | 2x+6y=96 | | y=6x^5+12x^3+6x^2-6x^3+7 | | 4(2t+1)=2(6t+5) | | 4(2t+1)=2(26t+5) | | 25x-4-19x=2(3x-4)+4 |